Utilization of Open Access Repositories for Visibility of Academic Publications by Lecturers in South-East, Nigeria - Orsu, Nkem Emilia (International Journal of Knowledge Content Development & Technology, 2019)
Abstract The study investigates the utilization of open access repositories for visibility of academic publications by lecturers in South-East, Nigeria. The specific objectives were to investigate the types of academic publications available, platforms used in self-archiving, level of satisfaction derived by lecturers with the contribution of open access repositories, challenges and strategies. It adopted descriptive survey design. Proportionate stratified sampling technique was used to draw a sample size of 418 from the total population of 4,187 lecturers. Questionnaire and observation check list were used for data collection. Frequency count, percentage, and mean score were used to analyze the data. The study revealed that there are enough academic publications available such as books, journals, projects, and thesis with the exception of handouts. It also revealed that Google Scholar, Research Gate and Open Access Journal were the main platforms lecturers use in self-archiving; while other platforms like Institutional Repositories, among others were minimally employed. Lecturers are less satisfied with the contribution of open access repositories. All the suggested challenges such as inadequate power supply, poor network, lack of awareness and inadequate research grants were all accepted. Similarly, all the suggested strategies for improving them were accepted. Recommendations were made based on the findings such as more awareness creation on importance of open access repositories; re-training of lecturers and provision of adequate ICT infrastructures that will improve the utilization of open access repositories by lecturers which could enhance the global visibility of academic publications from the Nigerian Universities. URL: http://ijkcdt.net/xml/22144/22144.pdf